Revisiting ligament-sparing lumbar microdiscectomy: When to preserve ligamentum flavum and how to evaluate radiological results for epidural fibrosis - Özay, Rafet; O?ur, Törel; Durmaz, Hasan Ali; Türkoğlu, Erhan; Çağlar, Yusuf Şükrü; Şekerci, Zeki; Sorar, Mehmet; Hanalioğlu, Şahin (Elsevier Science Inc, 2018)
OBJECTIVE: Preserving the ligamentum flavum (LF) during lumbar spine surgery can help to limit the extent of postoperative epidural fibrosis (EF), which is a potential cause of persistent leg pain. We present a retrospective analysis of microdiscectomy with preservation of the LF to evaluate the effects of the two LF mobilizing techniques (reflecting inferiorly or medially vs. removing completely) on EF and clinical outcomes. METHODS: Microdiscectomy was performed through a unilateral laminotomy in 93 patients (52 male, 41 female; mean age, 46 years; range, 25-65 years) with L3-L4 (n = 3), L4-L5 (n = 40), and L5-S1 (n = 50) lumbar disc herniation. Patients whose LF was removed were assigned to group 1 (n = 42), and patients whose LF was preserved by mobilizing it medially (n = 31) or inferiorly (n = 20) were assigned to groups 2 and 3, respectively. Follow-up visual analog scale (VAS) scores and magnetic resonance images were evaluated. RESULTS: EF scores, particularly for the anterior quadrants, were significantly higher in group 1 than in groups 2 (P = 0.012) and 3 (P = 0.001). Likewise, postoperative VAS scores in group 1 were also significantly higher than in groups 2 (P = 0.009) and 3 (P = 0.044). CONCLUSIONS: Our results demonstrate that 1) preserving the LF during lumbar microdiscectomy reduces the formation of postoperative EF and improves clinical outcomes; 2) EF in the anterior, rather than the posterior epidural space, is correlated with clinical results; and 3) the ligament mobilizing technique used should be individually tailored on the basis of the features of disc herniation.
WOS: 000432959600042
PubMed ID: 29530695
Keywords: Disc Herniation; Epidural Fibrosis; Ligamentum Flavum; Lumbar Spine; Magnetic Resonance Imaging; Microdiscectomy